CHALLENGES IN IMPLEMENTING LESSON STUDY AT HIGHER EDUCATION - Nur Fatimah (Universitas Negeri Padang, 2013)
Without ignoring changes including the one on curriculum, it is the fact that teaching and learning process remains showing similar but unique phenomena. One of the phenomena is related to the teaching practice in a large class. Teaching in a large class often results in problems on the material delivery to students and class management. The teacher is challenged to deal with the problems. Lesson study offers an alternative to deal with such problems. The study involves the teaching teacher as well as the colleagues, authority and students. The process including planning, doing and reflecting not only enhances teachers’ professional development but also improves classroom teaching and learning activities. Through this paper, the writer intends to elaborate challenges in implementing lesson study at higher education-English education in this case. The challenges range from the beginning when deciding to conduct the lesson study to the learning process and the peer discussion after teaching. Therefore, the points discussed here include the practice on conducting lesson study at an English classroom, the challenges and the solutions. It is expected that the shared ideas on the lesson study can be disseminated to the wider coverage of education.